Mixed Feelings : Emotional Phenomena, Rationality and Vagueness. - Ledwig, Marion, 1968- (De Gruyter, 2009)
This book opens up a new area of research by not only considering the rationality of such diverse phenomena as ordinary emotions, generalized anxiety disorder, social phobia, psychotic depression, major depressive disorder, and bipolar disorder, but also by evaluating the question whether the vagueness of these diverse disorders and emotions poses an obstacle to the rationality of these phenomena. As these emotional phenomena turn out to be vague on many different levels, an explanation is found for the millennia long dispute of which kind of phenomena fall under the emotions and whether such.